CD4+ T Cells Are Dispensable for Induction of Broad Heterologous HIV Neutralizing Antibodies in Rhesus Macaques - Sarkar, Sanghita; Spencer, David A.; Barnette, Philip; Pandey, Shilpi; Sutton, William F.; Basu, Madhubanti; Burch, Reuben E.; Cleveland, John D.; Rosenberg, Alexander F.; Rangel-Moreno, Javier; Keefer, Michael C.; Hessell, Ann J.; et al. (Frontiers in Immunology, 2021)
Induction of broadly neutralizing antibodies (bNAbs) is a major goal for HIV vaccine development. HIV envelope glycoprotein (Env)-specific bNAbs isolated from HIV-infected individuals exhibit substantial somatic hypermutation and correlate with T follicular helper (Tfh) responses. Using the VC10014 DNA-protein co-immunization vaccine platform consisting of gp160 plasmids and gp140 trimeric proteins derived from an HIV-1 infected subject that developed bNAbs, we determined the characteristics of the Env-specific humoral response in vaccinated rhesus macaques in the context of CD4+ T cell depletion. Unexpectedly, both CD4+ depleted and non-depleted animals developed comparable Tier 1 and 2 heterologous HIV-1 neutralizing plasma antibody titers. There was no deficit in protection from SHIV challenge, no diminution of titers of HIV Env-specific cross-clade binding antibodies, antibody dependent cellular phagocytosis, or antibody-dependent complement deposition in the CD4+ depleted animals. These collective results suggest that in the presence of diminished CD4+ T cell help, HIV neutralizing antibodies were still generated, which may have implications for developing effective HIV vaccine strategies.